The good liar [videorecording (DVD)] - Mirren, Helen; McKellen, Ian; Carter, Jim, 1948- (Warner Home Video, 2020)
Career con artist Roy Courtnay can hardly believe his luck when he meets well-to-do widow Betty McLeish online. As Betty opens her home and life to him, Roy is surprised to find himself caring about her, turning what should be a cut-and-dry swindle into the most treacherous tightrope walk of his life.